Perception and Attitude of Second-year Medical and Dental Students regarding the Use of a Problem-based Learning - Bista, Soni; Paudel, Sabita; Shrestha, Bijayata; Subedi, Nuwadatta; Basnyat, Rupesh Shingh; Chettri, Pradip (Journal of Nepal Health Research Council, 2024)
Backgrounds: Problem-based learning (PBL) is a learner-centered pedagogical approach in which a person learns about a subject by working in groups to solve an open-ended problem. The objective of the present study was to assess students' perceptions and attitudes toward Problem-based learning and the role of tutors in Problem-based learning.Methods: This quantitative study was conducted among second-year medical and dental undergraduate students from November 2022 to November 2023. The students were divided into eight groups, and each group was facilitated by tutors. A Problem-based learning tutor guide, with a case on the topic of diarrhea/dysentery, was designed as a module with six triggers and given to the groups. At the end of nine days of PBL sessions, feedback from students on the process of Problem-based learning and tutors was received using the 'Dolmans and Schmidt' and 'Dolmans and Ginns' questionnaires, respectively. The level of attitude of the students based on their feedback toward the Problem-based learning process and the tutors were also assessed. The data were entered into Microsoft Excel, and descriptive analysis was performed using the Statistical Package for Social Sciences (SPSS), version 21.Results: Among the 79 responses received, 72 (92.4%) students gave a good rating of the process of Problem-based learning, indicating a favorable attitude. The participants agreed with the themes based on the influence of discussion, content tested, course objectives, lectures, tutors, and reference literature. Similarly, 63 (81%) students gave a good rating of the tutorials’ performance, suggesting a favorable attitude. They agreed that tutors facilitated active, self-directed, contextual, and collaborative learning.Conclusions: This study revealed the positive perceptions and attitudes of medical and dental undergraduate students regarding the PBL process and the role of tutors in Problem-based learning. The outcomes of this study have provided a foundation for implementing Problem-based learning in Nepal's medical and dental undergraduate curricula.Keywords: Dental education; diarrhea; dysentery; medical education; problem-based learning.